Symmetry and efficiency - Fabella, Raul V. (1997)
We consider teams where information asymmetry (adverse selection and moral hazard) is minimized by entry point screening designed to produce homogenous membership and work group arrangements and job rotation that render effort at worst imperfectly observable. We show that under membership symmetry, budget balance and strict rationality, a self-enforcing Pareto efficient (cooperative) and envy-free solution is attainable if and only if the production technology is of a unique concave family. Even in the absence of moral hazard and adverse selection, a self- enforcing Pareto efficiency remains impossible outside this family.
Includes bibliographical references (page 109).
Keywords: Information asymmetry; Moral hazard; Job rotation